Commercial Micro-Credit, Neo-Liberal Agriculture and Smallholder Indebtedness: Three Bangladesh Villages. Issue 2 (15th March 2021) - Misra, Manoj
ABSTRACT: Evidence suggests that smallholders are fast becoming one of the largest micro-credit recipient groups in Bangladesh. However, the literature on the effects of micro-credit use among smallholders is surprisingly deficient. This article seeks to rectify this gap by highlighting the ramifications of micro-credit's foray into the subsistence agriculture sector. It analyses the ostensibly disparate processes of mounting smallholder indebtedness and the phenomenal rise of micro-finance institutions in Bangladesh in light of the country's broader context of agricultural commoditisation, input subsidy reduction and a systematic lessening of the subsidised agricultural credit system. The article uses the concept of "accumulation by dispossession/encroachment" to argue that persistent borrowing from micro-finance institutions (MFIs) exposes smallholders to the risks and volatilities of the market. Using qualitative insights from a case study of three villages, it demonstrates how the capital accumulation model of Bangladeshi MFIs marginalises smallholders and ensnares them in a perpetual cycle of debts.